Chemical composition, productive and economic performance of Nile tilapia under different feeding regimes - Chareo-Benitez, Berenice; Juárez-Barrientos, José Manuel; Álvarez-González, Carlos Alfonso; Kido-Cruz, Ma. Teresa; Alcántar-Vázquez, Juan Pablo (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of the present study was to evaluate the effect of different feeding regimens on productive and economic performance, and on the proximal-chemical composition of Nile tilapia. Four feeding regimens were designed considering the number of days fed per week, 7×0 (fed seven days a week), 6×1 (fed six days a week), 5×2 (fed five days a week) and 1×1 (alternating feeding, fed one day and not the next one). The period of dietary restriction lasted 36 days and subsequently fish were re-feeding for 24 days seven days a week. Growth was recorded every 12 days, estimating different productive parameters. An economic analysis taking into account the production costs was performed. Finally, the moisture, ash, lipid, protein and carbohydrate content of the Nile tilapia muscle was analyzed. At the end of the re-feeding period, a total wet weight compensation was observed for groups 6×1 and 5×2, and total length for groups 6×1, 5×2 and 1×1. The economic analysis recorded the highest increasing yields in group 5×2; while the group minimizing total variable costs was 1×1. The reduction in costs per unit of production between groups 7×0 and 1×1 was 15%. Chemical-proximal analysis revealed statistical differences for moisture content (7×0) and carbohydrate content (1×1). The groups 6×1 and 5×2 showed a total growth compensation, without negatively affecting muscle quality and/or final economic performance. The compensatory growth observed in the Nile tilapia allows to design feeding strategies to make its culture more efficient.
Keywords: Regional aquaculture; compensatory growth; financial profitability; food restriction; Nile tilapia